Navigating the Mind/body Divide: The Female Cannibal in French Films Grave ( Raw , 2016), Dans ma peau ( In My Skin , 2002) and Trouble Every Day (2001) - Dooley, Kathleen (Emerald, 2019)
Grave (English title: Raw), the 2016 feature film debut from French writer/director Julia Ducournau, is a body horror that explores cannibalism in a contemporary setting. A vegetarian student, Justine, develops cannibalistic desires after she is forced to eat rabbit kidneys in a hazing ritual at a veterinarian school.